Omvendt ordstilling i prosa og metrisk poesi - Gammelgaard, Lasse (Danske Studier, 2013)
This article claims that inversion in literary analysis and stylistics has not received the necessary nor sufficient amount of critical attention. It is suggested that this is due to the fact that metric poetry underwent a recession during the twentieth century. As a consequence of this, the stylistic feature of inversion became less frequent. It became marginalised and stigmatised. This article distinguishes between grammatical and ungrammatical inversion. Grammatical inversion is a rearrangement of the normal word order which does not, however, break the rules of the word-order system. It often consists of moving a sentence component (e.g. an adverbial phrase) to the very opening of a syntactic sentence (the Foundation Space, cf. Paul Diderichsen). Ungrammatical inversions are ones which violate the rules of a word-order system. They do so because metrical restrictions (such as metre and rhymes) trump syntax restrictions. In some cases ungrammatical inversion can generate ambiguity, because the sentence subject can be placed in the object’s position and vice versa. This ambiguity can have a decisive impact on the interpretation of the sentence.